Answer:
$3
Step-by-step explanation:
21 rand * ($1/7 rand) = $3
Answer:
d
Step-by-step explanation:
(7,1)
Answer:
$4.50
Step-by-step explanation:
Please give brainliest!!
Answer:
16
Step-by-step explanation:
First, substitute the values of the variables into the expression:
3(y + 4) - (x - 1)
3(2 + 4) - (3 - 1)
Now, simplify both parentheses:
3(6) - 2
18 - 2
Finally, simplify:
16
Note: √a * √a = a
√a * √b = √ab
(√2 + √10)² = (√2 + √10)(√2 + √10)
= √2(√2 + √10) + √10(√2 + √10)
= √2*√2 + √2*√10 + √10*√2 + √10*√10
= 2 + √20 + √20 + 10
= (2 + 10) + (√20 + √20)
= 12 + 2√20
√20 = √(4 *5) = √4 * √5 = 2√5
= 12 + 2√20 = 12 + 2(2√5)
= 12 + 4√5